Future perfect : confronting decisions about genetics - Andrews, Lori B., 1952- (Columbia University Press, 2001)
Andrews offers a new plan for making decisions as individuals and as a society based on emerging issues of ethics and science by providing the first detailed glimpse into how genetic testing can change your self-image, your relationships with loved ones, and your expectations about your children.